Conservation of Hindu Religious Lontar Manuscripts Through Lontar Digitization Website Information System in Tabanan Regency - Sudarsana, I Made (Jurnal Penelitian Agama Hindu, 2024)
Lontar as a cultural product is rich in meaning and raised the image of balinese traditions in the world civilization. The existence of lontar tradition nowadays in Tabanan Regency has a long and old history complemented by historical, religious, philosophical, medicinal, literary, and other great scientific values. This research aims to 1) conserve and digitize lontar in Tabanan Regency, and 2) create a website information system for digitizing lontar in Tabanan Regency. The research methods employed are palm conservation, system analysis, system planning, system design and system testing. The results of the research showed that 1) the conservation and digitalization of lontar was carried out in Tabanan can save the lontar, to keep it in a good condition, not damaged by termites or rodents, so it can continue to be passed on to the next generation as a reflection of the past about the medicine, ceremonies, religion, arts, and culture. 2) The lontar digitization website information system can be used as a guide for the public regarding lontar information and contents. In conclusion, the saving of Hindu religious lontar manuscripts through the lontar digitalization website information system in Tabanan Regency is carried out in the form of conservation and the creation of a lontar digitalization website information system, to make it accessible for the entire community online. In terms of culture, it can be passed down to the next generation as a form of cultural and religious preservation including medicine, ceremony, religion, art, and culture. The development of information system for the lontar digitization website is very good and important to save Hindu religious lontar manuscripts.